pРНК-гены актиномицетов, гомологичные генам pРНК-кластера Streptomyces globisporus 1912-2 - Полищук, Л.В.; Мацелюх, Б.П. (Фактори експериментальної еволюції організмів, 2014)
Aims. To study the spread of the rRNA-genes homologous fо analogous genes of S. globisporus 1912-2 in the genomes of actinomycetes. Methods. The program BLASTN 2.2.29 was used for in silico analysis of Internet base of dates NCBI (Microbial genomes). Results. Sequence gomologous on 82–99% to sequences of rRNA-genes of S. globisporus 1912-2, were detected in 100 actinomycetes strains from 28 different families. The greatest number of strains belonging to some families: Streptomycetaceae (17 species), Mycobacteriaceae (10 species), Micrococcaceae (10 species), Pseudonocardiaceae (9 species), Nocardiaceae (8 species), Micromonosporaceae (8 species). The majority of families (14 spesies) included only one such strain actinomycetes. Sequences homologous to the 5S rRNA-gene of S. globisporus 1912-2 were detected in chromosomes of 25 actinomycetes cultures. Conclusions. In silico analysis of the primary structures of rRNA-gene clusters in the genomes of 100 actinomycetes revealed the existence of the largest differences in structures and spreading of 5S rRNA-genes in the studied cultures.